A New Guide to Italian Cinema - Celli, C. author. aut Link
XIV, 234 p.
Keywords: This book is a complete reworking and update of Marga Cottino-Jones' popular A Student's Guide to Italian Film (1983, 1993) . This guide retains earlier editions' interest in renowned films and directors but is also attentive to the popular films which achieved box office success among the public.